Effects of Dietary Polyphenols from Olive Mill Waste Waters on Inflammatory and Apoptotic Effectors in Rabbit Ovary - Maranesi, Margherita (Animals (Basel), 2021)
SIMPLE SUMMARY: Circular economy strategies applied in the agro-food supply chain have recently been focused on new techniques for using agri-food by-products in animal nutrition. Rabbits efficiently convert plant proteins into foods rich in animal protein, therefore its meat, which contains numerous compounds, is potentially beneficial to human health and represents an excellent example of functional food. The residues obtained from the olive oil extraction process are a key source of phenolic compounds. In recent years, polyphenols have been used as dietary supplements to enhance animal health, welfare and performance, and to obtain functional foods of animal origin. Polyphenols enhance primary and total follicle number, and influence the inflammatory and apoptotic process by controlling and inhibiting pro-inflammatory cytokines (e.g., cyclooxygenase-2, interleukin-1beta, and tumor necrosis factor-alpha), and apoptotic factors (e.g., BCL2-associated X protein). Many health benefits of polyphenol consumption have not yet been determined, including the molecular and cellular mechanisms responsible for these actions at ovarian level. This paper highlights that dietary polyphenols, obtained from the olive oil industry, inhibit inflammatory and apoptotic activities in rabbit ovary, by modulating gene and protein expressions of cyclooxygenase-2 and BCL2-associated X protein, thus suggesting a direct involvement of these dietary compounds in mammalian reproduction. ABSTRACT: The aim of this study was to evaluate the effect of dietary polyphenols on the expression of the effectors involved in inflammation and apoptosis in rabbit ovary. New Zealand White female rabbits were fed a basal control diet (CTR), or the same diet supplemented with a polyphenolic concentrate (POL, 282.4 mg/kg) obtained from olive mill waste waters. The follicle counts and the relative mRNA (RT-qPCR) and protein (immunohistochemistry) expression of the effectors involved in inflammation (cyclooxygenase-2; interleukin-1beta; tumor necrosis factor-alpha, TNFA) and apoptosis (BCL2-associated X protein, BAX), detected in the ovaries of both groups, were examined. The POL diet increased the primary and total follicles number. Cyclooxygenase-2 gene expression was higher (p < 0.05) in the POL group than in the CTR group, whereas BAX was lower (p < 0.05) in POL than CTR. Immunohistochemistry revealed the presence of all the proteins examined, with weaker (p < 0.05) COX2 and BAX signals in POL. No differences between the CTR and POL groups were observed for IL1B and TNFA gene and protein expression. These preliminary findings show that dietary polyphenols modulate inflammatory and apoptotic activities in rabbit ovary, regulating cyclooxygenase-2 and BAX expression, thus suggesting a functional involvement of these dietary compounds in mammalian reproduction.